Correlation of Small Dense LDL Cholesterol and Apolipoprotein B with LDL Cholesterol and its Clinical Significance in Overweight, Type 2 Diabetes Mellitus and Coronary Artery Disease - Bhattarai, Arabinda Mohan; Batra, HS; Bandyopadhyay, Suchit; Misra, Pratibha; Sharma, Manushri; Agarwal, Deeprika (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Atherosclerotic Coronary Artery Disease (CAD) is fundamentally related to disorders of lipid metabolism. Health problems like obesity, glucose intolerance and metabolic syndrome increase atherosclerotic CAD risk. A fraction of Low density lipoprotein cholesterol (LDL) is called small dense low density lipoprotein cholesterol (sdLDL). These particles are more atherogenic because they are taken up more easily by arterial wall, readily oxidized and not easily cleared from plasma. Every LDL particle contain an Apo B molecule. Methods: In this cross sectional study we recruited 100 known cases each of CAD, type 2 diabetes, overweight and 100 age and sex matched healthy controls. We took a detailed case summary along with anthropometric measurements. We measured sdLDL by heparin magnesium precipitation method followed by direct estimation of the LDL in the supernatant. Result: Linear regressive analysis showed positive correlation between sdLDL and Apolipoprotein B (Apo B) with LDL cholesterol (r=0.61, p=0.004), (r=0.754, p=0.0034) respectively. Multiple Comparisons after Kruskalwallis test of sdLDL and Apo B levels of type 2 diabetes, CAD and overweight with controls were significant (p<0.001). Conclusion: Our findings suggest that the estimation of sdLDL and Apo B provide a complimentary benefit in assessment of cases with CAD, type 2 diabetes and overweight.